Modified band annuloplasty technique for functional tricuspid regurgitation repair in patients with grossly dilated annuli: The three‐suture junctional continuous suture band annuloplasty technique. Issue 4 (5th March 2019) - Xu, Hongfei; Davies, Henry; Zheng, Junnan; Peng, Teng; Ni, Yiming
Abstract: Functional tricuspid regurgitation (FTR) is the most common of all tricuspid dysfunctions. Ring annuloplasty is an effective treatment strategy for FTR. Currently, the most commonly used suture method for tricuspid ring annuloplasty is the interrupted U‐shaped suture method. However, when tricuspid annuli are grossly dilated (septal segments > 60 mm), interrupted sutures are insufficient in avoiding the folding over of the annulus or the tearing of sutures. Therefore, we recommend a new band suture technique; namely, the three‐suture junctional continuous suture band annuloplasty technique.